Lung function decline after mountain ultra-marathon is accompanied by reduced inspiratory pressure but not by detectable changes in CC16 - Antoine Raberin; Bastien Krumm; Tom Citherlet; Guia Tagliapietra; Tadej Debevec; Vincent Pialoux; Grégoire P. Millet (European Journal of Applied Physiology, 2026)
Purpose Mountain ultra-marathons (MUM) impose multiple stressors on pulmonary function inducing risk of airway epithelial damage. This study aimed to assess the magnitude of pulmonary function changes and the associated risks of airway damage induced by such a race. Methods Thirteen volunteers completed the MUM (330 km, 24,000 m elevation gain). Pulmonary function was assessed using standardized procedures before (pre-) and within 1 h after (post-) the race. Assessments included forced inhalation and exhalation maneuvers, as well as maximal inspiratory pressure (MIP) measurements. Venous blood samples were collected for the analysis of plasma club cell secretory protein 16 (CC16). Blood volume was determined using the carbon monoxide rebreathing method. Results From pre- to post-, forced vital capacity (FVC) (-7.5%, p = 0.001), forced expiratory volume in 1 s (FEV 1 ) (-12.2%, p = 0.002) and peak expiratory flow (-10.4%, p = 0.016) were reduced. MIP decreased by 14.5% (104 ± 29 vs. 90 ± 26 cmH₂O, p = 0.005). CC16 levels remained unchanged, even after normalization for plasma volume changes ( p = 0.929). Slope ratio and β-angle of the maximal expiratory flow-volume curve changes were not significant ( p = 0.101 and p = 0.055, respectively). Significant relationships showed that greater decreases in FVC ( r = − 0.60, p = 0.026) and FEV₁ ( r = − 0.62, p = 0.018) were associated with faster MUM completion times. Conclusion The acute negative impact of MUM on pulmonary function has been confirmed. The extent of this impairment appears to be proportional to race duration. Biomarker analysis suggests that airway epithelial integrity remains preserved. The reduced pulmonary function could be due to respiratory muscle fatigue.

Critical power and critical oxygenation: examining transferability between normoxia and hypoxia - Tomasz Kowalski; Kinga Rębiś; Adrian Wilk; Piotr Szwed; Andrzej Klusiewicz; Tadej Debevec; Raphael Faiss (European Journal of Applied Physiology, 2025)

Respiratory responses to hypoxia during rest and exercise in individuals born pre-term: a state-of-the-art review - Benjamin J. Narang; Giorgio Manferdelli; Grégoire P. Millet; Tadej Debevec (European Journal of Applied Physiology, 2022)

Do twelve normobaric hypoxic exposures indeed provoke relevant acclimatization for high-altitude workers? - Tadej Debevec; Grégoire P. Millet; Franck Brocherie (International Journal of Biometeorology, 2021)

Are five 60-min sessions of isothermic heat acclimation sufficient to elicit beneficial physiological adaptations? - Alexandros Sotiridis; Tadej Debevec; Nickos Geladas; Igor B. Mekjavic (European Journal of Applied Physiology, 2020)

On the climbing performance enhancing effects of New Zealand blackcurrant extract - Tadej Debevec; Ben J. Lee (European Journal of Applied Physiology, 2020)

Cardio-respiratory, oxidative stress and acute mountain sickness responses to normobaric and hypobaric hypoxia in prematurely born adults - Tadej Debevec; Vincent Pialoux; Mathias Poussel; Sarah J. Willis; Agnès Martin; Damjan Osredkar; Grégoire P. Millet (European Journal of Applied Physiology, 2020)

Separate and combined effects of 21-day bed rest and hypoxic confinement on body composition - Tadej Debevec; Tarsi C. Bali; Elizabeth J. Simpson; Ian A. Macdonald; Ola Eiken; Igor B. Mekjavic (European Journal of Applied Physiology, 2014)

Acute short-term hyperoxia followed by mild hypoxia does not increase EPO production: resolving the “normobaric oxygen paradox” - Tadej Debevec; Michail E. Keramidas; Barbara Norman; Thomas Gustafsson; Ola Eiken; Igor B. Mekjavic (European Journal of Applied Physiology, 2012)

Respiratory muscle endurance training: effect on normoxic and hypoxic exercise performance - Michail E. Keramidas; Tadej Debevec; Mojca Amon; Stylianos N. Kounalakis; Bostjan Simunic; Igor B. Mekjavic (European Journal of Applied Physiology, 2010)